A Case of Priapism with Risperidone - Ginory, Almari; Nguyen, Mathew (Case Reports in Psychiatry, 2014)
Priapism is a urologic emergency defined as a prolonged, possibly painful, penile erection. There are several known causes of priapism including psychotropic medications. One of the mechanisms by which antipsychotics are believed to induce priapism is through alpha-1 antagonism. This is case of a 50-year-old male with a history of schizophrenia with previous priapism related to trazodone, who presents with new onset priapism associated with risperidone. In this case, the treatment of priapism includes discontinuation of the offending agent and drainage of the corpus cavernosum twice along with intracavernosal phenylephrine injections. It is important to educate patients on priapism as a possible side effect of medications. It is also important to consider previous episodes of medication-induced priapism when prescribing psychotropic medications as this may increase the patient’s future risk of priapism.